Essential diabetes medicines and health outcomes in 127 countries. Issue 5 (31st January 2021) - Budhram, Dalton; Benipal, Simran; Bilimoria, Krish; Maraj, Darshanand; Wang, Ri; Persaud, Nav
Abstract: Aim: Diabetes is the ninth leading cause of death. Improving access to diabetes medicines may decrease mortality. Diabetes medicines on national essential medicines lists (NEMLs) vary considerably. We examine the association between diabetes population health outcomes relating to mortality and the listing of diabetes medicines on national essential medicine lists for 127 countries. Materials and methods: We conducted a cross‐sectional study. We determined the number of diabetes medicines on NEMLs and used multiple linear regression to analyse the association between diabetes health outcomes and the number of medicines on NEMLs. We used linear regression to assess the association between diabetes health outcomes and the listing of or not listing of medicines that were listed by 25‐75% of countries. Diabetes prevalence, gross domestic product (GDP) per capita and mean expenditure per person with diabetes were controlled for in all analyses. Results: The total number of diabetes medicines listed on NEMLs ranged from 0 to 16 (median: 4; interquartile range: 3‐6). Diabetes health outcome scores were associated with the number of diabetes medicines on NEMLs [1.3‐point increase (95% confidence interval, 95% CI 0.5‐2.1) for every additional medicine on NEMLs; P = .002] and GDP per capita [19.5‐point increase (95% CI 5.4‐33.6) for every 10‐fold increase in GDP; P = .003]. Diabetes expenditure was not associated with health outcome scores ( P = .23). Increases in diabetes health outcomes score were associated with the listing of glimepiride (7.9‐point increase, 95% CI 2.3‐13.5, P = .006) and glipizide (5.8‐point increase, 95% CI 0.03‐11.6, P = .049) on NEMLs. Conclusions: Listing of diabetes medicines on NEMLs has the potential to improve population health outcomes related to mortality in countries with diverse incomes and diabetes prevalence without necessarily increasing diabetes health expenditure.